Successful crossings with early flowering transgenic poplar: interspecific crossings, but not transgenesis, promoted aberrant phenotypes in offspring. Issue 8 (29th June 2014) - Hoenicka, Hans; Lehnhardt, Denise; Nilsson, Ove; Hanelt, Dieter; Fladung, Matthias
Summary In forest tree species, the reproductive phase is reached only after many years or even decades of juvenile growth. Different early flowering systems based on the genetic transfer of heat‐shock promoter driven flowering‐time genes have been proposed for poplar; however, no fertile flowers were reported until now. Here, we studied flower and pollen development in both HSP::AtFT and wild‐type male poplar in detail and developed an optimized heat treatment protocol to obtain fertile HSP::AtFT flowers. Anthers from HSP::AtFT poplar flowers containing fertile pollen grains showed arrested development in stage 12 instead of reaching phase 13 as do wild‐type flowers. Pollen grains could be isolated under the binocular microscope and were used for intra‐ and interspecific crossings with wild‐type poplar. F1‐seedlings segregating the HSP::AtFT gene construct according to Mendelian laws were obtained. A comparison between intra‐ and interspecific crossings revealed that genetic transformation had no detrimental effects on F1‐seedlings. However, interspecific crossings, a broadly accepted breeding method, produced 47% seedlings with an aberrant phenotype. The early flowering system presented in this study opens new possibilities for accelerating breeding of poplar and other forest tree species. Fast breeding and the selection of transgene‐free plants, once the breeding process is concluded, can represent an attractive alternative even under very restrictive regulations.